Synthesis of nano sized hydroxyapatite powder using sol-gel technique and its conversion to dense and porous bodies - Sopyan, Iis; Ramesh, Singh; Hamdi, Mohamed Salah (Scientific Publishers of India, 2008)
Hydroxyapatite powder has been prepared via sol-gel procedure using calcium nitrate tetrahydrate and diammonium hydrogen phosphate as the precursors for calcium and phosphorus, respectively. XRD measurement shows that the powder contains hydroxyapatite crystals with ß-TCP and calcium oxide as secondary phases. Hydroxyapatite powder of higher purity, i. e., the correct Ca/P ratio, has been obtained by adding an appropriate amount of diammonium hydrogen phosphate and heating with stirring. Morphological evaluation by SEM measurement shows that the particles of the HA are tightly agglomerated and globular in shape with an average size of 1-2 μm. The primary particulates have average diameters of 50-200 nm, as detected by SEM and nanoparticie sizer. Purity (almost 100%) of the obtained hydroxyapatite has been confirmed by XRD analysis. Its performance has been tested by making dense and porous samples.